Concordance of the frequency, typing, and results of high risk human papilloma virus in cervical cytology materials with biopsy: Retrospective analysis of 5604 patients (Annals of Medical Research, 2021)
None
Keywords: HPV; Cervix; Pap Smear; Cervical Intraepithelial Neoplasia.